2021
DOI: 10.1111/jth.15272
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism incidence and risk assessment in lung cancer patients treated with immune checkpoint inhibitors

Abstract: Background: There are scarce data on venous thromboembolism (VTE) rates among non-small cell lung cancer (NSCLC) patients treated with immune-checkpoint inhibitors (ICI). The Khorana Score (KS), used to guide thromboprophylaxis in cancer patients, was validated in patients receiving chemotherapy.Objective: To assess VTE rates and KS performance among NSCLC patients treated with ICI or chemotherapy. Methods:We performed a retrospective cohort study of NSCLC patients starting either ICI or platinum-based chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 40 publications
0
46
0
Order By: Relevance
“…Further evidence against the conclusion that ICIs are a clinically significant risk factor for cancer-associated VTE is presented in a retrospective analysis demonstrating that VTE occurred led frequently among lung cancer patients receiving an ICI than among those getting platinum-based chemotherapy. 25 It appears that, except for HLH (see below), PD-1, PD-L1 and CTLA-4 inhibitors are associated with hematological irAEs of similar rates, types, magnitudes and clinical courses. Because they are so infrequent, irAEs' predisposing factors, clinical presentations, mechanisms-of-toxicity, and management are uncertain.…”
Section: Targeted Therapeuticsmentioning
confidence: 99%
“…Further evidence against the conclusion that ICIs are a clinically significant risk factor for cancer-associated VTE is presented in a retrospective analysis demonstrating that VTE occurred led frequently among lung cancer patients receiving an ICI than among those getting platinum-based chemotherapy. 25 It appears that, except for HLH (see below), PD-1, PD-L1 and CTLA-4 inhibitors are associated with hematological irAEs of similar rates, types, magnitudes and clinical courses. Because they are so infrequent, irAEs' predisposing factors, clinical presentations, mechanisms-of-toxicity, and management are uncertain.…”
Section: Targeted Therapeuticsmentioning
confidence: 99%
“…The references in the relevant articles were also manually searched for related studies. Overall, 18 retrospective studies reporting incidences and/or outcomes of venous and/or arterial thrombosis in patients on ICIs [ 1 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and 4 additional relevant systematic reviews and meta-analyses [ 24 , 25 , 26 , 27 ] were identified and included in this review.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a Danish population cohort study showed a 6-month cumulative incidence of VTE of 4.1% (95% CI 2.3–6.7%) in patients receiving ICIs, comparable to 3.5% (95% CI 3.4–3.6%) found in those receiving chemotherapy [ 1 ]. In another study, Icht et al included 345 patients with NSCLC and reported a 6-month cumulative incidence of VTE of 7.1% in the chemotherapy cohort, compared with 4.5% in the ICI cohort (HR 1.6, 95% CI 0.6–3.9) [ 17 ]. However, as expected, the two cohorts were significantly different in baseline characteristics, including more metastatic disease and much less use as first-line therapy in the ICI cohort, which could have affected the results.…”
Section: Incidence Of Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…According to the score, patients are assigned into low-, medium-, and high-risk groups. However, almost all current relevant studies have found that KS is not efficient for identifying cancer patients suitable for VTE prevention ( Nichetti et al, 2019 ; Icht et al, 2021 ; Kewan et al, 2021 ; Moik et al, 2021 ). Only one study has shown that a KS ≥ 1 is significantly associated with VTE ( Sussman et al, 2021 ).…”
Section: Risk Factors For Tementioning
confidence: 99%